A Christian theology of science : reimagining a theological vision of natural knowledge - Tyson, Paul G. (Grand Rapids Baker Academic, 2022)
"Reframes the discussion between Christian theology and contemporary science, arguing that when Christians treat theology as their first truth discourse, it is good for both science and religion"--
Includes bibliographical references (pages 195-202) and index.
Keywords: Religion and science; Theology